The public is personal: reflections on the ethical dimensions of selfie research. Issue 2 (26th May 2020) - McGill, MARY
Abstract : Derived from the standards of feminist qualitative research, this methodological reflection develops 'the public is personal' as a mode of critical awareness for visual culture researchers working with social media data such as the selfie. Against the prevalent logic of 'but the data is already public', this paper draws on empirical and theoretical insights to argue that the publicness of digital data is no indication of an individual's consent to its use in contexts beyond how they originally intended. Rather than treating digital data as purely metric or divorcing it from its creator, researchers must be cognisant of the complex negotiations of privacy, agency, and subjectivity such artefacts represent. By centring the person behind the data, 'the public is personal' asserts the qualitative dimensions of publicly available digital data as key ethical considerations which defy generalities and require adaptive, reflexive responses.